Discurso e escrita de si na obra Hospício é Deus de Maura Lopes Cançado - Cordeiro, Solange (2014)
Much has been written about madness and crazy about , many writers have created characters in his works that delved into the tragic world of the asylum , but if these narratives such an experience is perceived next to ' off ' , the narratives written by the mad themselves can read a version of madness 'inside'. Ie, the eyes of those who lived the experience of internment in psychiatric hospitals and prepared speeches on such spaces and relations involving them. This case the work Hospice is God (1965) Maura Cançado Lopes, daughter of wealthy, traditional family, which spontaneously admitted for the first time in 1949, in Belo Horizonte. Later he moved to Rio de Janeiro where he began publishing short stories in the Journal of the Brazil and was admitted or was admitted several times to psychiatric institutions. Maura lived a significant part of his life in mental hospitals, one of which wrote a diary in the form of the said work, which is the official bank of the literary standard. Hospice is God , as well as other forms of expression ' crazy ' (in speeches , images or texts ) offer varied possibilities for understanding the relationships established in the mental hospital , on own medical knowledge about life and especially these guys called crazy . The main objective of this dissertation is to understand the discursive battle built around the life of Maura and her book is God Hospice , which is part of the speech itself which it had built , but considering other sources (such as storybook The Sufferer 's View and some letters sent by Maura ) , to understand the speeches Maura perceived as testimony of an era, the experience of madness and hospitalization in a specialized area , considering the relations of gender and power , as well as the construction of subjectivities